An evolutionary model of sensitive periods when the reliability of cues varies across ontogeny. (25th October 2021) - Walasek, Nicole; Frankenhuis, Willem E; Panchanathan, Karthik
Abstract: Sensitive periods are widespread in nature, but their evolution is not well understood. Recent mathematical modeling has illuminated the conditions favoring the evolution of sensitive periods early in ontogeny. However, sensitive periods also exist at later stages of ontogeny, such as adolescence. Here, we present a mathematical model that explores the conditions that favor sensitive periods at later developmental stages. In our model, organisms use environmental cues to incrementally construct a phenotype that matches their environment. Unlike in previous models, the reliability of cues varies across ontogeny. We use stochastic dynamic programming to compute optimal policies for a range of evolutionary ecologies and then simulate developmental trajectories to obtain mature phenotypes. We measure changes in plasticity across ontogeny using study paradigms inspired by empirical research: adoption and cross-fostering. Our results show that sensitive periods only evolve later in ontogeny if the reliability of cues increases across ontogeny. The onset, duration, and offset of sensitive periods—and the magnitude of plasticity—depend on the specific parameter settings. If the reliability of cues decreases across ontogeny, sensitive periods are favored only early in ontogeny. These results are robust across different paradigms suggesting that empirical findings might be comparable despite different experimental designs. Abstract : Phenotypic plasticity, the ability to tailor development to different conditions, typically declines with age. However, some traits have sensitive periods, windows of heightened plasticity, at later life stages, such as adolescence. The evolution of such windows is not well understood. Using mathematical modeling we find that changes in the reliability of information available to developing organisms may influence when sensitive periods evolve. Specifically, when the reliability of information increases across ontogeny, sensitive periods evolve later.